Epidemiology : A Very Short Introduction - Saracci, Rodolfo (Oxford Oxford University Press, 2010)
What is epidemiology? What are the causes of a new disease? How can pandemics be prevented? Epidemiology is the study of the changing patterns of disease and its main aim is to improve the health of populations. It's a vital field, central to the health of society, to the identification of causes of disease, and to their management and prevention. Epidemiology has had an impact on many areas of medicine; from discovering the relationship between tobacco smoking and lung cancer, to the origin and spread of new epidemics. However, it is often poorly understood, largely due to misrepresentations
Include Illustrations References and Index.
A Very Short Introduction.
Keywords: Epidemiology